Pesquisadores-docentes: formação e pesquisa a partir do olhar humboldtiano - Della Méa, Marco Aurélio Antunes (2024)
This Doctoral Thesis is linked to the Postgraduate Program in Education at the Federal University of Santa Maria (UFSM), line of research “Teaching, Knowledge and Professional Development” and had as its thematic inspiration the Brazilian public university from the post -graduation stricto sensu and the ideas of Wilhelm Von Humboldt regarding human formation (Bildung) and research, principles that had as their motto regional development and the moral strengthening of the German nation, implemented at the University of Berlin. The research question was “what is the possibility of an interface between innovation and science in research and human training (Bildung) in the current Brazilian stricto sensu postgraduate course?”. The general objective of the Thesis was to analyze the nodal points of the Brazilian university in the emerging context of innovation and science and the ideas of regional development, and the moral strengthening of the nation led by the University of Berlin. The analysis covered the study of stricto sensu postgraduate studies as an emerging context for the improvement of Brazilian higher education in the 21st Century, having as the study's guiding thread its evolutionary process, demarcating aspects of approach/departure from Humboldtian ideas about universities and the explicit objective there, of innovation and science. The historical process of the Brazilian Public University, although partially inspired by such ideas, moved away from contemplating the practical needs of implementing and expanding Higher Education, public and free, with a wide range of vacancies in all areas of knowledge, since the decade from 1960 to the present day. The current field of training and research in stricto sensu postgraduate studies was considered with an emphasis on the emerging context of innovation and science in current Brazilian education from the perspective of high-level teaching researchers. For the University of Berlin, the trait of innovation consisted of research intertwined with pedagogical practice, however current Brazilian developments, based on the experience of teaching researchers, pointed to other contexts, such as collaborative work in national and international research networks and the pragmatic vision of science. However, was this enough for regional development and the moral strengthening of the Brazilian nation? To delve into the intricacies of the main question and derivations of the research process, the research planning started from the scope of qualitative and quantitative research in education, applied in case studies and conducted by descriptive-interpretative analysis. The data were produced from the record of teaching production; exploratory questionnaire and interviews using Google Forms, allowing a range of information for the argumentative construction of the final analysis of the reality studied. The conclusions proved to be restricted, since the percentage of adherence by high-level teaching researchers (PQ) to the invitation to participate was shown to be between 10% and 15% of the population of postgraduate programs scored by CAPES Concepts 6 and 7. Thus, in the presentation and discussion of the results, the maximum possibilities were sought to analyze and understand what drives these programs within the Brazilian Public University, free, but of quality projected by national and international rankings and not translated into the evidence that was sought in light of Humboldtian ideas.